Comparison of Isozymes and Quantitative Traits for Evaluating Patterns of Genetic Variation in Purple Needlegrass ( Nassella pulchra ) - Eric E. Knapp; Kevin J. Rice (Conservation Biology, 1998)
Decimation of the California (U.S.A.) prairie has increased interest in the conservation and ecological restoration of grasslands composed of native perennial species. Widespread plantings are being attempted, and the potential for contaminating existing remnant populations with maladapted germplasm has led to concerns about the use of nonlocal seed sources. We evaluated regional patterns of isozyme and quantitative trait variation in the native perennial grass Nassella pulchra for the purpose of developing recommendations about the spatial scales over which seed can be translocated. Seed was collected from 10 remnant native populations. Progeny from all 10 populations were scored for isozyme variation with 11 stains, and progeny from 8 populations were planted in a common garden to evaluate variation for 11 quantitative (polygenic) traits. The correspondence between isozyme and quantitative trait variation and the relationships of both types of variation to geographic distance and climate were explored by Mantel test regressions. Populations were strongly differentiated for both isozymes and quantitative traits, but cluster analysis based on each type of data did not result in the same population groupings. This lack of congruence was further demonstrated by the nonsignificance of the regression of Hedrick’s distances for isozymes on Mahalanobis distances for quantitative traits. Quantitative trait variation was strongly associated with climatic variables, whereas isozyme variation was not. This suggests that the relative importance of genetic drift and selection in shaping patterns of genetic differentiation may depend upon the type of trait evaluated. Quantitative traits are potentially better indicators of adaptation to regional and local environmental variation, and thus the usefulness of isozymes for making recommendations about the spatial scales over which seed of N. pulchra can be translocated may be limited. Unfortunately, obtaining data on patterns of quantitative trait variation is often time‐ and labor‐intensive. The close association of quantitative trait variation with regional climatic variables indicates that an index based on readily obtainable climatic information might aid restorationists in making rapid decisions about appropriate spatial scales for translocating native grasses. Compariciones de Isozimas y Rasgos Cuantitativos para Evaluar Patrones de Variación Genética en el Pasto‐Aguja Morado ( Nasella pulchra) La disminución de la pradera de California (USA) ha incrementado el interés en la conservación y restauración ecológica de pastizales compuestos por especies perennes nativas. La dispersión amplia de siembras se ha intentado y el potencial de contaminación de poblaciones remanentes con germoplasmas mal adaptados ha generado preocupaciones sobre el uso de fuentes de semilla no locales. Evaluamos patrones regionales de variación de isozimas y variación cuantitativa de rasgos en el pasto perenne nativo Nasella pulchra con el propósito de desarrollar recomendaciones sobre las escalas espaciales en las cuales las semillas pueden ser movidas. Las semillas fueron colectadas a partir de 10 poblaciones remanentes nativas. Las progenies de las 10 poblaciones fueron evaluados para variación de isozima usando 11 colorantes y las progenies de 8 poblaciones fueron plantadas en un jardín común para evaluar la variación de 11 rasgos (poligenéticos) cuantitativos. La correspondencia entre variaciones de isozimas y de rasgos cuantitativos y las relaciones de ambos tipos de variación con distancia geográfica y clima fue explorada usando pruebas de regresión de Mantel. Sin embargo, los análisis de conjunto basados en cada tipo de datos no dió como resultado las mismas agrupaciones de poblaciones. Esta carencia de congruencia fue demonstrada más adelante por la no significancia de la regresión de distancias de Hendrick para isozimas en distancias Mahalanobis para rasgos cuantitativos. La variación en rasgos cuantitativos estuvo fuertemente asociada con las variables climáticas, mientras que la variación de isozimas no lo estuvo. Esto sugiere que la importancia relativa de la deriva génica y de la selección en patrones de forma de diferenciación genética pueden depender del tipo de rasgo evaluado. Los rasgos cuantitativos son potencialmente mejores indicadores de adaptación a la variación ambiental local y regional, por lo tanto la utildad de isozimas para hacer recomendaciones sobre escalas espaciales en las cuales las semillas de N. pulchra pueden ser movidas puede verse limitada. Desafortunadamente, la obtención de datos de patrones de variación de rasgos cuantitativos require frecuentemente de tiempo y esfuerzo intensivos. La asociación cercana de variación de rasgos cuantitativos con variables climáticas regionales indica que un indice basado en información climática accesible podría ayudar a los restauradores a tomar decisiones rápidas sobre escalas espaciales apropiadas para mover pastos nativos.